Navigating the patriarchal politics of institutions: Positioning women and gender equality at the center of agricultural development institutions - Njuki, Jemimah; Kaaria, Susan; Kangogo, Ednah; Macharia, Kenneth; Malapit, Hazel J.; Mboo-Tchouawou, Michèle; Tanaka, Sonja (Springer, 2024)
While the lens of patriarchy has been used to understand the gendered power dynamics at different levels of society, research and development organizations have not been subjected to the same analysis. This chapter explores the gendered nature of organizations, using four key elements of patriarchal organizations (i) a gendered division of labor and tasks, (ii) gendered hierarchies, (ii) rigid rules governing performance, and (iv) privileging male dominated content and processes. We discuss the implications of these characteristics on women’s engagement in research, as well as on the positioning of gender research in organizations. Using two case studies, we discuss the key ways in which organizations can be more transformative. Although different organizations are implementing strategies to address gender inequalities in organizations, including through workplace policies and mentoring and leadership programs, we conclude that these initiatives fall short of addressing the structures within organizations and that perpetuate gender-based discrimination.